The HIV/AIDS Surveillance System in Gresik Health Office - Hary Chandra; Sholikah Sholikah (Health Notions, 2018)
Introduction. Issues of HIV/AIDS cases, that tend to increase every year, require comprehensive prevention and controling efforts through promotion, early detection and treatment, and rehabilitation. These efforts need to be supported by precise and accurate data and information through a good surveillance system. Gresik was one of five districts in East Java with the highest AIDS cases reported. Purpose. The purpose of this study was to describe HIV and AIDS surveillance system in Gresik District Health Office based on system component analysis. Method. This study was an evaluation research. The subject of this study was the HIV and AIDS case surveillance system that was carried out in Gresik District Health Office in 2016. Respondents in this study were the Head of Communicable Disease Control and Prevention, the recording and reporting officer of Gresik District Health Office, and 16 officers in HIV AIDS program at selected Public Health Centers (PHC). Descriptive analysis described the components of ongoing HIV/AIDS surveillance system in Gresik District Health Office and the results obtained were compared with the theory and national guidebook for management of HIV and AIDS programs. Results. Based on the human resources (HR) input component that involved in the HIV/AIDS surveillance system, most health workers had a health diploma degree (D3) level education. In process component, for level B health facilities, data collection was difficult due to lack of trained laboratory personnels. Most of of respondents (84.8%) said data processing was easy because it was helped by HIV/AIDS and Sexually Transmitted Infections Information System (SIHA) application. However, reporting accuracy was 65% and not timely. The analysis process was only carried out at the Health Office level. In the output component, dissemination was carried out monthly. Feedback or request for data improvements to health facilities was done monthly on the second week of the following month. Conclusion. The ongoing HIV/AIDS surveillance system in Gresik still needs improvement in the implementation based on the national guidebook for management of HIV and AIDS programs. Keywords: HIV/AIDS, Surveillance system, Evaluation